Morfofunctional parameters in judo's fight - Campos, Ítalo Sérgio Lopes (2017)
Considering the complexity of judo and the ample energy and neuromuscular demands, a whole process of competitive preparation must be directed to different physical capacities allowing the athlete to perform his combat actions with the best suitability possible. Mapping the  behaviour of a judo athlete from observations of behaviour units  in a real fighting situation would be a way of trying to identify the best topography or the best "aptitude" to achieve victory. The present investigation analysed the judo from the interactions of a real competition situation, aiming to verify, between winners and losers, possible differences or correlations between anthropometric parameters, motor performance and functional behaviours in a competitive situation. The results showed that: a) the experience is decisive between winning or losing; b) leg techniques are the most used between winners and losers, and losers use them more frequently; c) there are different strategies between fights; d) The energy cost in judo depends on the configuration of the fights. It is believed that such results can help coaches and athletes in guiding and rationalizing the training process in relation to performance determinants in judo.